2005
DOI: 10.1029/2004gl020966
|View full text |Cite
|
Sign up to set email alerts
|

Observed variability of the South Pacific westward sea level anomaly signal in the presence of bottom topography

Abstract: [1] This study investigates the behavior of westward propagating sea level anomalies across the South Pacific Ocean, with a focus on the long Rossby wave signal determined from filtered TOPEX/Poseidon and ERS satellite altimeter data. An evaluation of the energy variability of the signal using a two-dimensional Radon Transform analysis suggests that Rossby waves interact with both ridges and seamounts at various locations across the basin. Anomalously slow Rossby wave phase speeds are found over steep, isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 16 publications
5
19
0
Order By: Relevance
“…7c). In contrast, no real bathymetric influence is apparent at 13°S, 177°W across the Kermadec Ridge, where Maharaj et al (2005) found slow Rossby wave speeds. The extended theory curves are well represented by the mean flow configuration, which also best models the energy observed (Fig.…”
Section: Tropicsmentioning
confidence: 51%
See 3 more Smart Citations
“…7c). In contrast, no real bathymetric influence is apparent at 13°S, 177°W across the Kermadec Ridge, where Maharaj et al (2005) found slow Rossby wave speeds. The extended theory curves are well represented by the mean flow configuration, which also best models the energy observed (Fig.…”
Section: Tropicsmentioning
confidence: 51%
“…This suggests that the energy accounted for by the extended theory contains a large contribution from its representation of the mean flow. We also note that the southwest Pacific basin contains very complicated bathymetry, which may lead to more localized or regional variability (Killworth and Blundell 1999;Maharaj et al 2005). The large improvement in energy explained by the extended theory in the Western Subtropics compared with Fig.…”
Section: Basin-wide Maps Of First To Fourth Baroclinic Mode Energy Ramentioning
confidence: 73%
See 2 more Smart Citations
“…Chelton and Schlax (1996) first used the RT to study the characteristics (especially the phase speed) of westward-propagating planetary waves in satellite altimeter data. Since then, several authors have applied the 2-D RT on SST or SLA datasets (Hill et al, 2000;Maharaj et al, 2004Maharaj et al, , 2005Cipollini et al, 2001Cipollini et al, , 2006. Superimposed propagating signals locally extracted by the 2-D RT are generally interpreted as various baroclinic modes of Rossby waves (Maharaj et al, 2004;Cipollini et al, 2006).…”
mentioning
confidence: 99%